Espectro ensanchado - Poveda Zafra, José Noé (Ingeniería, 1999)
The manufacturers of wireless communications equipment continuously look for new techniques to increase the capacity of the channels, that every day are more congested by the great demand of new users. One of the fields that are investigated more are the techniques of multiple access, where many users share a frequency band because a bandwidth does not exist to assign a permanent frequency channel to each user. This article shows the techniques of widened Phantom SS (of the English Spread Spectrum) that allows the simultaneous use of an ample band of frequencies by many users by means of techniques of multiple access by division of code CDMA (of the English Code Multiple Division Access), to increase in great proportion its capacity in relation to the conventional techniques of multiple access.